Finishing the Last Lap: Experimental Evidence on Strategies to Increase Attainment for Students Near College Completion. (15th September 2022) - Bettinger, Eric P.; Castleman, Benjamin L.; Choe, Alice; Mabel, Zachary
Abstract: Nearly half of students who enter college do not graduate. The majority of efforts to increase college completion have focused on supporting students before or soon after they enter college, yet many students drop out after making significant progress towards their degree. In this paper, we report results from a multi‐year, large‐scale experimental intervention conducted across five states and 20 broad‐access public colleges and universities to support students who are late in their college career but still at risk of not graduating. The intervention provided these "near‐completer" students with personalized text messages that encouraged them to connect with campus‐based academic and financial resources, reminded them of upcoming and important deadlines, and invited them to engage (via text) with campus‐based advisors. We find little evidence that the message campaign affected academic performance or attainment in either the full sample or within individual higher education systems or student subgroups. The findings suggest low‐cost nudge interventions may be insufficient for addressing barriers to completion among students who have made considerable academic progress.